(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Rebenok V. Using informatively-communication technologies by the teachers of high school in educational process. The article reviews the process of using informatively- communication technologies by the high school teachers in the educational process that provides the transmission of knowledge and access to various educational information of students.